Penegakan Hukum Terhadap Perdagangan Telur Penyu - Apridyanita Pratiwi Tarigan; La Syarifuddin; Agustina Wati (Fakultas Hukum Universitas Mulawarman, 2020)
ABSTRACT This study discusses a law enforcement against the trade of sea turtle eggs in Samarinda. Sea turtles emerge as part of endemic animals in Indonesia in which their existence is almost extinct based on the Government Regulation, Number 7 Year 1999. This study employed a socio-legal (socio-legal research/law in contex) approach, namely a case study on empirical legal research in the form of community legal behavior. The existence of the trade of sea turtle eggs in Samarinda can still be encountered in the area located on Jl. Pangeran Antasari. The results of this study indicated that the legal protection on the sea turtle population, due to the rampant trade of sea turtle eggs in Samarinda, was not completely carried out. It is shown by the fact that the turtle egg trade in Samarinda still exists. Additionally, the law enforcement against the perpetrators of the turtle egg trade is not optimally implemented in which it is proven by the fact that the court merely imposes a light sanction and does not perceive ecological aspects. Keywords: Enforcement, Protection, Trade, Sea Turtle Eggs